O efeito da carga oclusal no processo de reparo do ligamento periodontal após reimplante imediato em molar de ratos: avaliação histológica e imunoistoquímica - Beneti, Igor Mariotto [UNESP] (2012)
An ideal protocol treatment for cases of immediate or delayed tooth replantation hasn’t been developed yet, although tooth replantation is considered the best treatment in cases of tooth avulsion. Factors like extra-alveolar time, storage, contamination, dental rizogenesis phase, use of a splint, and occlusal trauma can interfere in the replantation prognosis. The normal occlusal function is a mechanical stimulus that is necessary for the maintenance of the homeostasis of periodontal tissue, whereas the absence or excess of occlusal load results in a disharmonic functioning of periodontal tissues. The aim of this study is to assess the influence of occlusal load during the repair process of immediate and delayed replantation of rat molars. They used 280 Wistar rats divided into three groups (normal occlusion, and infraocclusion supraoclusão) and a control group total, they were divided into nine periods. Qualitative and quantitative analysis will be performed in histological cuts, using the hematoxylin eosin staining protocol, and cells that display immunoreactivity to cellular apoptosis. The data will be submitted to variance analysis A or Kruskal-Wallis), using SPSS 16.0 at a significance level of p<0.05. In the initial period the thickness of the cervical third of the PDL of replanted teeth showed a statistically significant increase in all test groups, compared to the control group. A percentage reduction of blood vessel area, cell profile and PDL thickness was observed in the majority of studied periods. The supra-occlusal group showed a higher level of radicular resorption, followed by the normal and infra-occlusion groups. In face of the limitations of this study, it was concluded that the occlusal load absorbed by replanted teeth modifies the repair process of the PDL. Occlusal trauma accelerates the radicular resorption of replanted teeth significantly.